Design, Implementation, and Evaluation of a Distance Learning Framework to Adapt to the Changing Landscape of Anatomy Instruction in Medical Education During COVID-19 Pandemic: A Proof-of-Concept Study - Naidoo, Nerissa; Azar, Aida J.; Khamis, Amar Hassan; Gholami, Mandana; Lindsbro, Marjam; Alsheikh-Ali, Alawi; Banerjee, Yajnavalka (Frontiers in Public Health, 2021)
This study presents the design of a DL-framework to deliver anatomy teaching that provides a microfiche of the onsite anatomy learning experience during the mandated COVID-19 lockdown. First, using nominal-group technique, we identified the DL learning theories to be employed in blueprinting the DL-framework. Effectiveness of the designed DL-framework in anatomy teaching was demonstrated using the exemplar of the Head and Neck (H&N) course during COVID-19 lockdown, in the pre-clerkship curriculum at our medical school. The dissemination of the DL-framework in the anatomy course was informed by the Analyse, Design, Develop, Implement, and Evaluate (ADDIE) model. The efficiency of the DL-framework was evaluated using the first two levels of Kirkpatrick’s model. Versatility of the DL-framework was demonstrated by aligning its precepts with individual domains of key learning outcomes framework. The framework’s blueprint was designed amalgamating principles of: Garrison’s community inquiry, Siemens’ connectivism and Harasim’s online-collaborative-learning; and improved using Anderson’s DL-model. Following the implementation of the DL-framework in the H&N course informed by ADDIE, the framework’s efficiency was evaluated. In total, 70% students responded to the survey assessing perception towards DL (Kirkpatrick’s Level:1). Descriptive analysis of the survey results showed that the DL-framework was positively received by students and attested that students had an enriched learning experience, which promoted collaborative-learning and student-autonomy. For, Kirkpatrick’s Level:2 i.e., cognitive development, we compared the summative assessment performance in the H&N course across three cohort of students. The results show that the scores of the cohort, which experienced the course entirely through DL modality was statistically higher (P<0.01) than both the other cohorts, indicating that shift to DL did not have an adverse effect on students’ learning. Using Bourdieu’s Theory of Practice, we showed that the DL-framework is an efficient pedagogical approach, pertinent for medical schools to adopt; and is versatile as it attests to the key domains of students’ learning outcomes in the different learning outcomes framework. To our knowledge this is the first-study of its kind where a rationale and theory-guided approach has been availed not only to blueprint a DL framework, but also to implement it in the MBBS curriculum.